Hvad er Hecuba for dig? Om en teaterkritisk forskel - Kuhlmann, Annelis (Peripeti, 2016)
In Danish history of theatre, especially shortly after World War II, the theatre critic, Frederik Schyberg (1905-50), and the theatre director, Sam Besekow (1911-2001), were both focused on cultural-ethical sides of criticism in theatre. They were occupied by the critical imperative to theatre professionals in order to offer a renewed consciousness to the spectators about the function of theatre art in Danish post war society. Both Besekow and Schyberg had a theatrical gaze on the impact of their profession. When dealing with the ethical side of critical aspects of theatre they took their point of departure from a reading of Shakespeare’s Hamlet, where the play in the play is preceded with Hamlet asking the actor about what Hecuba is to him, and he to Hecuba.